Analysis of Publishing Services Seafarers Identity Documet (SID) At the One-Stop Service Center at the Harbormaster's Office and Tanjung Perak Main Port Authority - Darma Aulia Rahman; Dian Junita Arisusanty; Femmy Asdiana; Rizqi Aini Rakhman (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the Analysis of Seafarers Identity Document (SID) Issuance Services at the One-Stop Service Center at the Tanjung Perak Main Port Authority Office. SID is an official identity document for seafarers who work on foreign-flagged vessels and serves to ensure access and legal protection for them. SID issuance services are carried out online through the e-SID website which is designed to increase efficiency and ease of service for seafarers. To evaluate the quality of these services, this research uses a quantitative method with a descriptive approach. Data were collected through questionnaires involving service users and then analyzed based on five dimensions of service quality: Tangibles, Empathy, Assurance, Responsiveness, and Realibility. The results show that the SID issuance service at KSOP Utama Tanjung Perak with an average satisfaction score of 76.32% is classified as good. The Empathy dimension obtained the highest score (80%), followed by Assurance (76.83%), Responsiveness (75.75%), Reliability (75%), and Tangibles (73.12%). Some aspects that require improvement include information availability, friendly attitude of officers, time efficiency, and consistent application of SOPs. As an effort to improve service quality, researchers recommend developing a real-time application status tracking feature, socializing online procedures through educational media, periodic training for officers, and improving information technology infrastructure. With these steps, it is expected that SID issuance services will become more efficient, transparent, and responsive to seafarers' needs.